2020
DOI: 10.1002/er.5146
|View full text |Cite
|
Sign up to set email alerts
|

Indirect thermosiphon flat‐plate solar collector performance based on twisted tube design heat exchanger filled with nanofluid

Abstract: Summary Stationary solar collector such as flat‐plate collector is a thermal device, which traps solar energy and converts it into heat that can be used in industrial and domestic applications such as water heating. Flat‐plate collector thermal performance enhancement is investigated in this research paper. Two cross‐sectional geometries of the tube in the heat exchanger were investigated; a normal circular tube and a twisted tube were used in the experiment. The aim of the twisted tube exchanger is to enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Circulation can be achieved when a heat source alters the density of a particular fluid, which makes the low‐density fluid higher, and when it loses its heat, the same process will circulate. Thermosiphon FPSC is famous because it does not require a mechanical pump, which means that there is no need for an electrical energy source near the collector 141 . Thermosiphon FPSC thermal efficiency is lower than the forced circulation of FPSC because thermosiphon FPSC needs a high‐temperature difference between the inlet and the outlet of the collector to create a circulation.…”
Section: Energy Efficiency Of Thermosiphon Fpscmentioning
confidence: 99%
See 2 more Smart Citations
“…Circulation can be achieved when a heat source alters the density of a particular fluid, which makes the low‐density fluid higher, and when it loses its heat, the same process will circulate. Thermosiphon FPSC is famous because it does not require a mechanical pump, which means that there is no need for an electrical energy source near the collector 141 . Thermosiphon FPSC thermal efficiency is lower than the forced circulation of FPSC because thermosiphon FPSC needs a high‐temperature difference between the inlet and the outlet of the collector to create a circulation.…”
Section: Energy Efficiency Of Thermosiphon Fpscmentioning
confidence: 99%
“…However, if the concentration has reached a specific value, the efficiency will begin to decrease; Chougule et al 142 stated that the critical concentration was 0.6 vol% of CNT. Eltaweel et al 141 argued that changing the heat exchanger inside the thermosiphon FPSC from circular tubes to twisted tubes would increase the effectiveness of using carbon‐based nanofluid.…”
Section: Energy Efficiency Of Thermosiphon Fpscmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar water heating systems have shown in many ways to reduce hot water energy consumption significantly. One primary concern that has attracted much research is the solar water heaters' low energy conversion efficiency (Deng et al, 2019;Eltaweel, Abdel-Rehim and Hussien, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the maximum thermal conductivity (2311 W/m·K) and minimum thermal resistance (0.67 K/W) were obtained in a horizontal situation. Eltaweel et al 24 tested the thermal performance of the flat‐plate solar collector utilizing a twisted tube to enhance the heat transfer. Also, the performance with normal circular tubes was compared.…”
Section: Introductionmentioning
confidence: 99%